Copyright: Policies, Resources, and Questions for School Librarians - Dotson, Kaye; Parker, Kathy; Thomas, William Joseph (My University, 2022)
School librarians are often the professionals in their schools responsible for helping faculty and students locate, use, and create content responsibly. This article shares data from an East Carolina University survey of common copyright questions, background knowledge, availability of resources, and policy in North Carolina school libraries. Copyright and fair use resources are discussed, and three sample scenarios are presented.
Keywords: School Media Center Coordinators; Professional Development; Copyright; Fair Use